Application of process mapping for digitization of mechanical parts with 3D laser scanner - Piratelli Filho, Antonio (2018)
This work presents a systematization method for digitization of mechanical parts with threedimensional (3D) laser scanner using the process mapping method. The application involves the use of the IDEFØ methodology of process mapping to address the sequence of steps required to obtain the computer-aided design (CAD) model of the measured part. The variables involved in the setup and measurement with 3D laser scanner were investigated and applied to regular and free-form parts, and the parameter geometry, texture, light reflection and procedure of data acquisition were considered in the analysis. The software commands used to create the CAD models were also included and the ones related to mesh and surface creation were detailed. The systematized measurement planning was graphi graphically presented, and it proved useful to operators during the digitization process.